EFFECTIVENESS OF VEGETABLE CULTIVATION ACTIVITIES TO SUPPORT FOOD SECURITY AT CLASS IIB WONOGIRI CORRECTIONAL INSTITUTION - Sinulingga, Rizq Adyatma; Soge, Markus Marselinus (Universitas Nusa Cendana, 2026)
This study examines efforts to support food security through vegetable cultivation by utilizing prison land at the Class IIB Wonogiri Correctional Institution. The program is part of an agricultural independence initiative aimed at increasing food reserves, anticipating potential food crises, and contributing to Indonesia’s food self-sufficiency. The research uses a qualitative approach, with data collected through observation, interviews, and document studies, and analyzed through data reduction, presentation, and conclusion drawing. The analysis is based on program effectiveness theory and food security theory. The findings show that the program has been implemented by optimizing available land and cultivating relatively easy-to-grow vegetables such as kale, spinach, and eggplant. The harvest is used to supplement the nutritional needs of inmates, indicating that the program contributes positively to institutional food security. However, several obstacles hinder its sustainability, including pest attacks, soil fertility issues, and sanitation challenges. In addition, limited budget allocation creates uncertainty, as the continuity of the program depends on the outcomes of previous harvests. Therefore, improvements in resource management, agricultural support, and funding stability are necessary to ensure the long-term effectiveness of the program. Keywords: Effectivenes; Self-Reliance Development; Food Security; Vegetable Cultivation